Prevalence of lymphedema using large data sets: an epidemiological analysis in the United States and in Italy - Grigorean, Alexandru; Voci, D.; Farmakis, I. T.; Hobohm, Lukas; Keller, Karsten; Kucher, N.; Luchsinger, I.; Micieli, E.; Schievano, E.; Barco, S.; Fedeli, U. (Lymphology, 2023)
There is a lack of large epidemiological studies focusing on the prevalence of lymphedema. Vital registration data from the United States (US) (1999-2020) and Veneto, Italy (2008-2021) were analyzed. Lymphedema-related deaths were identified using disease-specific ICD-10 codes and served to estimate the burden of disease in the general population. We studied (i) the lymphedema-specific proportionate mortality as a proxy of the disease-specific prevalence, (ii) the prevalence of lymphedema in key patient subgroups, and (iii) age and sex-specific mortality rates. The prevalence of lymphedema increased over the last two decades with marked sex-specific differences: in the US, the estimated prevalence of lymphedema was 2.7 per 10,000 deaths for women and 1.5 per 10,000 deaths for men. In Veneto, the prevalence was 3.0 per 10,000 deaths for women and 1.1 per 10,000 deaths for men. The prevalence of lymphedema was 2- to 20-times in specific subgroups of patients, including those with obesity, skin infections, hypertension, diabetes mellitus, breast/gynecological cancers, and venous thromboembolism. The estimated prevalence of lymphedema is 2- to 3- times higher than previously thought and has been increasing for the past two decades. These results will serve as a reference for future research in this field.